Introduction (Archives of Criminology, 1974)
Approaching the 30 years of the the Polish People’s Republic from the point of view of the problems, which are the subject of research work, conducted by the Department of Criminology of the Institute of the Law Sciences at the Polish Academy of Sciences, one should be well aware of the fact, that during that period there could be noticed in many capitalist countries a marked increase of delinquency, and the explanation that is as a rule given for this phenomenon is the influence of, industrialization and urbanization processes. A marked increase has also taken place as regards, serious crimes, combined with aggression and in some countries, where the degree of industrialization is especially high, the phenomenon of organized crime (organized, specialized groups of criminals) has recently adopted alarming dimensions.In addition to this there can almost everywhere be found an increase in juvenile delinquency and that of young adults. This increase takes prace also in such milieux where disturbances of the socialization process are not connected with the bringing up of children in bad material conditions.In Poland, despite the fact that during those 30 years revolutionary economic transformations have taken place and enormous socio-demographic changes, often combined with intensified migration processes, there has not been noticed an increase in crime as compared with the pre-war period, but rather a marked decrease. Worth emphasizing is above all the drop by five times of homicides, the considerable decrease in the number of brawls and severe bodily injuries. According to statistical data the number of larcencies brought before a court has decreased markedly. It has, however, to be borne in mind that part of petty theft is at present settled in work enterprises through “exerting educational influence” and some, of course, is not revealed, as is the case in all countries. Even if we assume that among economic offences, of which statictics lists only a very small number, there is an especially large dark number, it should, however, be borne in mind, that as a rule these offences of an economic nature cause in practice only small material losses. Discussing data connected with robberies, it is worth while to stress that during the prewar period they used to be of a much more serious nature.An analysis of data from 1951 does not point to an increase in offences in Poland during that long period and in particular what deserves special emphasis, there is no increase in juvenile and young adult delinquency and also no intensification of delinquency among the inhabitants of towns and cities in comparison with the rural population. Studies have revealed that the differences in the intensity of delinquency between the various areas (voivodeships) is above all due to the social results of the mass migrations of the population, which started in 1945, and not to the industrialization and urbanization processes which are taking place. The greatest intensity of delinquency can be noticed in those areas with the largest percentage of newcomers, while in the most strongly urbanized and industrialized area (Katowice) the intensity of delinquency was and continues to be below the average fon the whole of Poland.Despite the systematic growth of industrialization and urbanization processes no increase in delinquency can be noticed or the increase is not significant at all, or appears only during the stage when industrial enterprises are under construction and later decreases markedly. On the basis of experience obtained in a newly established industrial centre (Nowa Huta) one may assume that in those few regions marked by intensive industrialization, where delinquency has distinctly increased, it is going to decrease later to the average level. The example of, Nowa Huta testifies to the fact that delinquency grew only during the first period of the influx of rural population, migrating into this area, which had lost the ties with its former environment and had thus been deprived of social control. Their adaptation to new difficult conditions of existence and new types of work proceeded with the accompaniment of considerable disturbances.The above findings are of great significance in the present conditions of new socio-political system, where it is possible to control many social phenomenaexerting an influence on crime.*The Departament of Criminology of the Institute of the Law Sciences, Polish Academy of Sciences conducts ‒ on the basis of statistical data ‒ systematic research on the dimensions and intensity of delinquency in Poland and their socio-economic as well as demographic conditioning, a problem to which a number of publications has been devoted. An analysis of the results of these researches makes it possible to throw a light on the entire problem in a manner that markedly differs from the current opinion on the determinants of criminal offences in the new socio-political conditions.A problem to which since the beginning in 1953 of the existence of the Department of Criminology many research works have been devoted, due to its specific significance, is that of social maladjustment of children and juvenile delinquents. This subject matter goes beyond the problem of juvenile delinquency alone, since it is connected with delinquency of a considerable section of the young adult offenders and persistent recidivists, even in older age groups, where the process of social maladjustment as a rule reaches back to the time when they were under age.Research connected with juvenile delinquents took into account the population of children from the lower grades of primary school (approximately 5,500 children), so important from the point of view of prevention of crime, as well as that category of youth, so far not examined in Poland, who “do not attend school and do not work” (542 boys and girls).The results of such investigations revealed the important and as a rule underestimated role played by maladjustment in school in the etiology of social maladjustment as well as the considerable percentage of school youth with symptoms of demoralization in the younger (below 12) age groups (about 11 per cent), due to which there arose the problem of earlier diagnosis of the above-mentioned symptoms in the school, which is of particular significance for the prevention of later juvenile delinquency on the part of these children.The population of juvenile delinquents, examined in great detail, was made up of approximately 1,700 juvenile delinquents from the Warsaw area and several other towns and settlements; in two-thirds of the cases researches were conducted during a long follow-up period. Subject of research were also 250 gangs of juvenile delinquents, who had committed larcency and hooligan offences.Studies of the juvenile delinquents revealed interaction, essential from the prognostic point of view, between the early beginnings of social maladjustment and the dimensions of recidivism of a later period, jointly with the period after the age of 21. Research of this type also points to the significance for the etiology of social maladjustment and juvenile delinquency of being brought up in negative family surroundings (especially excessive drinking of alcohol in such families), and also to the significance that should be attached to the early detection of personality disonders, frenquently encountered with such minorsThe problems of young adults (between 17 and 20), close to that of the juvenile delinquents, socially considered just as important, has also been taken into account in the studies of the Department of Criminology, regarding the intensity and dynamics of their delinquency and analyses of the type of offences committed by them. Detailed studies concentrated on this problem, dealing with several youth populations, which have committed offences combined with aggression and the large category of young adults showing tendencies for recidivism. Due to the specific features of youth, those who have committed offences and are below 21 years of age, require separate treatment and therefore problems, connected with tchem should be the subject of special research. Investigations conducted in the Department of Criminology base itself on the assumption that a joint discussion of young adult delinquency and the delinquency of older age groups ‒ something we often encounter ‒ may lead to an entire numer of faulty conclusions and incorrect decisions.Though larcency is the major offence committed by young adults, nevertheless there are very frequent offences combined with aggression. And it is actually for this reason that this category of young adults, committing the last mentioned offence have become the subject of studies, especially the prisoners convicted for offences qualified as hooligan offences and those convicted for robbery. The total material collected concerned approximately 1,000 young adults, who had been brought before a court for hooligan offences. In 300 cases detailed studies were conducted, combined with environmental interviews, which took into account the prisoners as well as their families. These studies revealed that there was a large numer of young adults who had committed hooligan offences, who had already in their childhood shown symptoms of severe social maladjustment and who had started very early to drink systematically alcohol. Anyhow, similar symptoms could be found with young adults convicted for robbery.Special research was devoted to problems of recidivism in the case of young adult offenders, combined with a long follow-up period. Attention concentrated on those who were convicted several times and as a rule came from among the former juvenile delinquents.In addition to this, studies were conducted of the further fate of young adult prisoners, set free in 1961 from 40 penitentiaries; the follow-up period lasted for l0 years; the examined population was made up of 2,000 men. The material obtained made it possible to establish with accuracy the dimensions of their later recidivism. The research under discussion testifies also to the necessity to deal with recidivism among young adults in connection with their earlier social maladjustment, often dating back to their childhood.The problem, of very early social maladjustment also turned out to be most essential as regards young prostitutes, who were the subject of separate and thorough studies.The problem of recidivism, thrown so clearly into relief in research on juvenile and young adult delinquents, was also taken into account in the case of adult offenders. Research of the Department of Criminology embraced several populations of recidivists, beginning with the young age groups (21-24 years old). Material was obtained about over 600 recidivists, out of which approximately 400 prisoners were subjected to thorough criminological and psychological studies. Recently started examinations of material connected with persistent recidivists, who had been sent to “centre for social adjustment” (a preventive detention centre).The studies of recidivists which were conducted revealed that the problems of recidivism should be dealt with in our country in connection with the phenomenon of systematic excessive drinking: a very considerable percentage of recidivists are individuals who, due to long lasting and frequent drinking of alcohol, have developed symptoms of dependency on alcohol. As a result of this the criminality is in the case of alcoholics among the recidivists connected with their addiction and general social degradation. An analysis of data obtained through psychological and medical studies, testifies to the fact that persistent recidivists not only reveal symptoms of early social maladjustment, but as a rule also distinct severe personality disorders, which make it necessary to introduce measures, taking into account the psychopathological features of those offenders. Underestimation of this problem causes in practice highly negative phenomena. Worth stressing are the results of research, revealing that the small number of recidivists with multiple convictions, who began their criminal careers when at least already 25 years old, almost always come from among alcoholics..           Due to the significance of systematic excessive drinking and that of alcoholism in the genesis of various negative social phenomena, the problem of alcoholism has been taken widely into account in research conducted by the Department of Criminology. However, special attention has recently been devoted to the subject of early alcoholism and its serious social repercussions,  underestimated so far and very little studied. In connection with this, research has been undertaken, conducted with 150 alcoholics up to 25 years old, who had been brought before social and medical commissions for alcoholics.Taken into account in research connected with excessive drinking were also people convicted for hooligan offences (approximately 600 from various age groups), 900 men charged with disturbing public order while intoxicated and people who had time and again been in a Detoxication Centre (500 men and 250 women). The obtained results testify to the importance of what is called problem of drinking. An analysis of the data about the law-breaking of these people showed that as a rule we deal here with people charged with offences that are not particularly severe; similar results have been revealed by material dealing with approximately 800 alcoholics who underwent treatment ‒ serious offences on the person are rare occurrences.*Investigations on criminological problems were conducted by taking into account sociological, psychological and psychopathological as well as legal aspects. In addition to subject matter, dealing with the dimensions of the criminality and its macro-social conditioning, empirical research concentrated mainly on the establishment of the etiology of social maladjustment in various samples of offenders by means of a detailed analysis of the individual cases, with a simultaneous utilization of objective data from various sources. Examination of long follow-up periods permitted the proper verification of prognostic factors.The results of the studies are being published since 1960, mainly in ,,Archiwum Kryminologii’ (Archives of Criminology), issued by the Departmentof Criminology which has so far printed 37 works, containing the results of empirical research. Some of the results of the Departments works have been published in other magazines and in the form of monographs.It should be stressed that the work of the Department of Criminology also includes opinions regarding drafts of laws, connected with the problem of delinquency, alcoholism and other phenomena in the field of social pathology; these opinions were sent to the proper ministries and to the parliament.Due to the great lack of scientific workers in the whole country, who are properly prepared to conduct research and to lecture in the field of criminology, the Department of Criminology has recently started postgraduate courses in this field.